Editorial - Mani, Alice (Ushus Journal of Business Management, 2021)
This edition of Ushus comprises papers and research material from several academic viewpoints and insights. The wide ranging scope that management and commerce possess is reflected in the extensive content and subject matter visible herein. Various academicians, professionals and researchers with varying areas of interest and specialization have been able to contribute generously to this issue. A brief overview of the 10 papers published in this issue make it evident that several articles on conventional well practiced domains extend to rapidly changing commercial scenarios consequential of unpredictable characteristics and newly established areas of commercial interest. Tomy Kallarackal's detailing of the Value Added Tax System and Jalpa Majmudar's presentation on Transfer Pricing cover two distinct but nevertheless crucial aspects of taxation and its recent evolution with regard to changing and improving business regulations.